Evaluation of radiation shielding features of Co and Ni-Based superalloys using MCNP-5 code: Potential use in nuclear safety - Sayyed, M. I.; Faras, Q. M.; Mahmoud, K. A.; Lacomme, E.; Kaky, K. M.; Khandaker, Mayeen Uddin *; Faruque, M. R. I. (mdpi, 2020)
Due to their excellent heat resistance, superalloys are used predominantly in the manufacturing of engine parts and accessories for aircraft and aerospace equipment. The Monte Carlo simulation (MCNP-5) code was performed to estimate the mean track length of the incident photons inside six different alloys. Then, based on the simulated track length, other important γ-ray shielding parameters were calculated. In this study, the highest mass attenuation coefficient was obtained for alloys encoded MAR-302 and MAR-247 and varied in the range 0.035–72.94 and 0.035–71.98 cm2 ·g −1, respectively. The lowest mass attenuation coefficient was found for alloys coded Inconel-718 and Nimocast-75 with a range of 0.033–59.25 and 0.32–59.30 cm2 ·g −1, respectively. Use was made of a recently developed online program Phy-X/PD to calculate the effective atomic number, equivalent atomic number, and the buildup factors for the alloys of interest. The effective removal cross-section for the fast neutron was also calculated for the studied alloys: the highest value was found for the alloys coded with Inconel-718 (P R = 0.01945 cm2 ·g −1) and Nimocast-75 (P R = 0.01940 cm2 ·g −1), and the lowest value was obtained for alloy coded MAR-302 (P R = 0.01841 cm2 ·g −1 ). Calculated data indicate that MAR-302 and MAR-247 are superior candidates for shielding of gamma-rays, while Inconel-718 and Nimocast-75 MAR-302 are suitable for the shielding of fast neutrons.